Could effective fracture toughness of polycrystalline aggregates exceed inner grain fracture toughness by adjusting toughness of grain boundary?. (14th April 2023) - Zhou, Junjie; Chen, Yanxi; Feng, Huawei; Chen, Huihan; Yu, Xingzhe; Liu, Bin
Abstract: Obtaining intergranular and transgranular fractures through grain boundary engineering has been considered an efficient technique that improves the effective fracture toughness of polycrystalline aggregates. In this paper, the idealized hexagonal microstructure, random microstructures, and microstructures of grains with large aspect ratios are analyzed through a semi-analytical approach and the cohesive finite element method. The results indicate that when the aspect ratio of grains is not too large, the crack paths consisting of intergranular and transgranular fractures are approximately Mode I fracture morphologies among these microstructures. As the ratio of toughness between grain boundaries and grains varies, the effective fracture toughness of the microstructure can be increased more than the grain boundary fracture toughness but cannot exceed the inner grain fracture toughness. In contrast, the microstructure of grains with a large aspect ratio leads to deflected crack paths that are unexpectedly obtained, which implies that the approximate Mode-I intergranular fracture along transverse direction is almost impossible. The results demonstrate that the projected energy dissipation rate along the direction perpendicular to the loading axis can be significantly improved beyond the inner grain fracture toughness by enlarging the aspect ratio of the grains. Nevertheless, the mixed-mode effective fracture toughness is still limited to the grain fracture toughness. Corresponding experiments are also carried out to qualitatively verify the numerical results. The underlying mechanism for this deflection of fracture path is due to the strong anisotropy of fracture toughness. The higher the grain aspect ratio, the greater the anisotropy of the macroscopic effective fracture toughness. The energy favored fracture path is determined by the largest ratio between the driving force and the toughness of fracture over all directions. Therefore, cracks cannot propagate in the direction of the maximum fracture toughness when the aspect ratio of the grain is sufficiently large. The fracture diagrams that vary with the aspect ratio of grain and the ratio of fracture toughness between the grain and grain boundary are provided. The results can provide valuable guidance for designing microstructures and improving fracture toughness in materials. Highlights: Effective fracture toughness of the microstructure can be higher than the grain boundary toughness but cannot exceed the inner grain toughness. Deflected crack path is achieved unexpectedly when the aspect ratio of the grain is high. The fracture diagrams that vary with the aspect ratio of grain and the ratio of fracture toughness between the grain and grain boundary are provided.